Faktor-Faktor yang Mempengaruhi Petani dalam Berusahatani Nilam (Pogostermon Cablin Benth) di Desa Lawada Kecamatan Sawerigadi Kabupaten Muna Barat - Muhsinin, Muhsinin; Nalefo, La; Arimbawa, Putu (Department of Agribusiness, Halu Oleo University, 2018)
This study aims to: Know the factors that affect farmers in patchouli farming in the Village Lawada Sawerigadi District West Muna. The population in this study is all patchouli farmers in Lawada Village Sawerigadi District West Muna Regency as many as 275 families. The sample in this research use arikunto formula that is simple random sampling with simple error rate 15%. So the overall sample amounted to 35 respondents. The results of this study indicate Factors affecting farmers in patchouli farming include variable land area, capital, advice friends and family, extension of extension, the number of farmers who have patchouli farming and the availability of input simultaneously / jointly significant effect on the production of patchouli. Partially, only the variable of capital, the recommendation of friends and family and the extension agent that significantly influence the production variables while the land area, the number of farmers in patchouli farm and the availability of input have no significant effect on the production veriabel. Then the relationship between production to income that affects income variables include production variables simultaneously / together significant effect on income vareabel and Partially (alone), production variables also have a significant effect on income variable.